1996
DOI: 10.1111/j.1439-0523.1996.tb00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of diploid and triploid interspecific hybrids between Lilium longiflorum and L. concolor by ovary slice culture

Abstract: Ovary slice culture, after cut-style poUination, was used to develop interspecific hybrids between Lilium longiflorum and L. concolor. Reciprocal crosses between diploid cultivars (2n = 2x = 24) were carried out. On the days 30, 35,40 and 45th after pollination (DAP), ovaries were sliced and cultured on a modified hormone-free Murashige-Skoog (M-S) medium without NH4NO3, supplemented with 6% sucrose, 50 mg/l yeast extract and 0.25% gelrite at pH 6.3. For the L. longiflorum X L. concolor cross, ovule germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
4
13
0
1
Order By: Relevance
“…This finding was used to identify the genome constitution in Darwin hybrid tulips. In other studies, when there were morphological differences in single-chromosome morphology between parental genotypes, hybrids were readily verified in genus Allium (Keller et al, 1996) and Lilium (North & Wills, 1969;Okazaki et al, 1994;Fernandez et al, 1996;Obata et al, 2000;Marasek & Orlikowska, 2001). Chromosome size also served as a trait for verification of hybrids between Cucurbita pepo L. and Cucurbita martinenzii (Metwally et al, 1996) and somatic hybrids Oriza sativa + Hordeum vulgare (Kisaka et al, 1998).…”
Section: Karyology Of Tulipsmentioning
confidence: 96%
“…This finding was used to identify the genome constitution in Darwin hybrid tulips. In other studies, when there were morphological differences in single-chromosome morphology between parental genotypes, hybrids were readily verified in genus Allium (Keller et al, 1996) and Lilium (North & Wills, 1969;Okazaki et al, 1994;Fernandez et al, 1996;Obata et al, 2000;Marasek & Orlikowska, 2001). Chromosome size also served as a trait for verification of hybrids between Cucurbita pepo L. and Cucurbita martinenzii (Metwally et al, 1996) and somatic hybrids Oriza sativa + Hordeum vulgare (Kisaka et al, 1998).…”
Section: Karyology Of Tulipsmentioning
confidence: 96%
“…El efecto del 2,4-D podría estar relacionado con la inducción de la respuesta morfogenética, ya que la degradación de esta auxina es más lenta cuando los explantos se incuban en oscuridad (Arzate Fernández et al, 1998).…”
Section: Inducción De Callos Y De Proembriones Somáticosunclassified
“…Hitherto various techniques have been applied successfully to overcome pre-and post-fertilization of incompatibility. For example, it has been reported that prefertilization barriers can be bypassed by using methods such as the cut style technique, the grafted style method, plant growth regulator treatment, and in vitro pollination (Van Tuyl et al 1988, 1991Li and Niimi 1995;Niimi et al 1999); post-fertilization barriers can be overcome by embryo rescue techniques such as embryo culture (Okazaki et al 1994), ovule culture (Niimi et al 1996), ovules-withplacental-tissue culture (Obata et al 2000), and ovary slice culture (Kanoh et al 1988;Fernández et al 1996;Arzate-Fernández et al 1998;Chi 2002).…”
Section: Introductionmentioning
confidence: 98%